Fatores de risco para metástases em linfonodos não-sentinela com câncer de mama e linfonodo sentinela positivo - Henrique Silva Bartels (2010)
BACKGROUND: According to the standard of care for breast cancer patients, complete axillary lymph node dissection (ALND) is performed when sentinel lymph node (SLN) presents metastasis. However, 40 to 70% of patients with positive SLN are found to have no other metastasis in non sentinel lymph node (NSLN) and the value of complete axillary lymph node dissection (ALND) has been questioned. The aim of our study was to evaluate risk factors for NSLN metastasis in patients with positive-SLN. PACIENTS AND METHODS: We reviewed 326 cases of patients with breast cancer and positive-SLN divided into two groups according to the nodal involvement in the ALND: patients with all NSLN negative for metastasis and patients with at least one positive NSLN. Clinical features of the patients, pathological features of the primary tumor (tumor size, histological tumor type and grade, mitotic index, nuclear grade, invasion of blood and lymphatic vessels, estrogen and progesterone receptors status) and SLN (number of positive and negative SLN, detection method of metastasis and size of the largest metastasis) were assessed. Data were submitted to univariate and multivariate logistic regression to evaluate the risk of metastasis in the NSLN, followed by construction of a mathematical model (nomogram) to predict the presence of additional disease in the non-SLN of these patients. The accuracy of the proposed nomogram was measured by the area under (AUC) the receiver operating characteristic curve (ROC curve).RESULTS: The univariate and multivariate analyses identified the following risk factors for involvement of NSLN with the respective p values: size of the largest SLN metastasis (p < 0.001, p = 0.002), number of positive SLN (p = 0.006, p = 0.04) and number of negative SLN (p = 0.01, p = 0.004). Invasion of lymphatic vessels showed p values of 0.075 and 0.085 (not statistically significant) but was also included in the nomogram. The nomogram showed an accuracy of 70% (AUC = 0.70).CONCLUSIONS: Our data showed that size of the largest SLN metastasis and number of positive and negative SLN were predictive risk factors for metastatic involvement of NSLN in patients with positive-SLN. These data must be informed in the SLN report. Our nomogram, similar to other models, may represent an additional tool to help physicians and patients who decide whether or not a complete ALND should be performed.